Jahresbericht des Vereins Kunsthalle Bern 1995. - Hahnloser, Bernhard; Loock, Ulrich; Kunsthalle Bern (Bern : Kunsthalle Bern, 1996)
Pettibon, Raymond ; Chablais, Vincent ; Marek, Raoul ; Schmid, Laurent ; Schwab, Verena ; Zussau, Véronique ; Hume, Gary ; Koch, Udo ; etc.
Duits
boek